Hair fiber characteristics and methods to evaluate hair physical and mechanical properties - Maria Valéria Robles Velasco; Tania Cristina de Sá Dias; Anderson Zanardi de Freitas; Nilson Dias Vieira Júnior; Claudinéia Aparecida Sales de Oliveira Pinto; Telma Mary Kaneko; André Rolim Baby (Universidade de São Paulo, 2009)
The hair thread is a natural fiber formed by keratin, a protein containing high concentration of sulfur coming from the amino acid cystine. The main physical proprieties of the hair depend mostly on its geometry; the physical and mechanical properties of hair involve characteristics to improve: elasticity, smoothness, volume, shine, and softness due to both the significant adherence of the cuticle scales and the movement control (malleability), as well as the easiness of combing, since they reduce the fibers static electricity. The evaluation of these effects on hair may be carried out by several methods, as: optical and electron microscopy, mechanical resistance measuring, shine evaluation and optical coherence tomography (OCT). O cabelo é uma fibra natural formada por queratina, uma proteína composta por teor elevado de enxofre proveniente da cistina. As propriedades principais do cabelo dependem de sua geometria, estrutura física. Características físicas e mecânicas das fibras capilares envolvem propriedades que melhoram: elasticidade, maciez, volume, maleabilidade, facilidade para o ato de pentear e brilho. A avaliação de tais propriedades do cabelo pode ser obtida por métodos diversos, como: microscopia óptica e eletrônica, mensuração da resistência mecânica, determinação do brilho e tomografia por coerência óptica (OCT).